Mobile Assisted Language Learning (MALL): Exploring the Students’ Experience on Listening Activities - Marsika Sepyanda; Dini Deswarni; Havid Ardi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
The impact of Covid-19 disease requires the educational process have to be implemented in an integrated way with technology. Mobile Assisted Language Learning (MALL) as the recent methods becomes more popular because of these, where everything can be simplified by using mobile devices. This research aims at exploring the use of Mobile Assisted Language Learning (MALL) on students’ listening activities especially related to their leaning experience. This research investigated the use of various applications and learning resources that can be accessed by students by themselves. It also gave a description about the students’ experience in using the applications on their listening activities which is considered as learning activity that is integrated Mobile Assisted Language Learning (MALL) on the process. This study was designed as descriptive quantitative research. The participants involved in this study were 33 English Department students who taken listening subject. Questionnaire was used as instrument in collecting the data in this stud, and it was distributed by using Google form. It was found that Mobile Assisted Language Learning (MALL) support students’ listening activities through several recommended applications. Most of the students got better learning experience on their listening activities through exercises that they got from the applications they used. It means that Mobile Assisted Language Learning (MALL) brings a great learning experience on students’ listening activities. Therefore, it can be concluded that Mobile Assisted Language Learning (MALL) support students’ listening activities through several recommended applications.